Analiza efektu IGARCH oraz efektu długozasięgowych zależności w szeregu stóp zwrotu indeksu WIG - Galin, Kamila (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article considers the impact of non-stationarity in rates of return series on estimated parameters of the GARCH(1,1) model and dependency structure analysis. The sum of the estimated coefficients α₁ + β₁ very close to one (the IGARCH effect) and long range dependence in absolute log-returns might be spurious. The possible explanation of the effects mentioned are shifts in the unconditional variance. The analysis of log-returns on the WIG index (using the adaptive weights smoothing method) suggests the presence of shifts in the unconditional variance, which is probably the reason for IGARCH and LRD effects. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 110-118